Systematic identification of secondary bile acid production genes in global microbiome - Yuwei Yang; Wenxing Gao; Ruixin Zhu; Liwen Tao; Wanning Chen; Xinyue Zhu; Mengping Shen; Tingjun Xu; Tingting Zhao; Xiaobai Zhang; Lixin Zhu; Na Jiao (mSystems)
ABSTRACT Microbial metabolism of bile acids (BAs) is crucial for maintaining homeostasis in vertebrate hosts and environments. Although certain organisms involved in bile acid metabolism have been identified, a global, comprehensive elucidation of the microbes, metabolic enzymes, and bile acid remains incomplete. To bridge this gap, we employed hidden Markov models to systematically search in a large-scale and high-quality search library comprising 28,813 RefSeq multi-kingdom microbial complete genomes, enabling us to construct a secondary bile acid production gene catalog. This catalog greatly expanded the distribution of secondary bile acid production genes across 11 phyla, encompassing bacteria, archaea, and fungi, and extended to 14 habitats spanning hosts and environmental contexts. Furthermore, we highlighted the associations between secondary bile acids (SBAs) and gastrointestinal and hepatic disorders, including inflammatory bowel disease (IBD), colorectal cancer (CRC), and nonalcoholic fatty liver disease (NAFLD), further elucidating disease-specific alterations in secondary bile acid production genes. Additionally, we proposed the pig as a particularly suitable animal model for investigating secondary bile acid production in humans, given its closely aligned secondary bile acid production gene composition. This gene catalog provides a comprehensive and reliable foundation for future studies on microbial bile acid metabolism, offering new insights into the microbial contributions to health and disease.IMPORTANCEBile acid metabolism is an important function in both host and environmental microorganisms. The existing functional annotations from single source pose limitations on cross-habitat analysis. Our construction of a systematic secondary bile acid production gene catalog encompassing numerous high-quality reference sequences propelled research on bile acid metabolism in the global microbiome, holding significance for the concept of One Health. We further highlighted the potential of the microbiota-secondary bile acid axis as a target for the treatment of hepatic and intestinal diseases, as well as the varying feasibility of using animal models for studying human bile acid metabolism. This gene catalog offers a solid groundwork for investigating microbial bile acid metabolism across different compartments, including humans, animals, plants, and environments, shedding light on the contributions of microorganisms to One Health.